Adherence to Early Antiretroviral Therapy: Results From HPTN 052, a Phase III, Multinational Randomized Trial of ART to Prevent HIV-1 Sexual Transmission in Serodiscordant Couples. (1st June 2015) - Safren, Steven A.; Mayer, Kenneth H.; Ou, San-San; McCauley, Marybeth; Grinsztejn, Beatriz; Hosseinipour, Mina C.; Kumarasamy, Nagalingeswaran; Gamble, Theresa; Hoffman, Irving; Celentano, David; Chen, Ying Qing; Cohen, Myron S.
Abstract : Background: Combination antiretroviral therapy (ART) for HIV-1–infected individuals prevents sexual transmission if viral load is suppressed. Methods: Participants were HIV-1–infected partners randomized to early ART (CD4 350–550) in HPTN052 (n = 886, median follow-up = 2.1 years), a clinical trial of early ART to prevent sexual transmission of HIV-1 in serodiscordant couples at 13 sites in 9 countries. Adherence was assessed through pill count (dichotomized at <95%) and through self-report items. Predictors of adherence were mental health and general health perceptions, substance use, binge drinking, social support, sexual behaviors, and demographics. Viral suppression was defined as HIV plasma viral load <400 copies per milliliter. Adherence counseling and couples' counseling about safer sex were provided. Logistic and linear regression models using generalized estimating equation for repeated measurements were used. Findings: Through pill count, 82% of participants were adherent at 1 month and 83.3% at 1 year. Mental health was the only psychosocial variable associated with adherence [pill count, odds ratios (OR) = 1.05, 95% confidence intervals (CIs): 1.00 to 1.11; self-report parameter estimate, OR = 0.02, 95% CI: 0.01 to 0.04], although regional differences emerged. Pill count (OR = 1.19, 95% CI: 1.10 to 1.30) and self-report (OR = 1.42, 95% CI: 1.14 to 1.77) adherence were associated with viral suppression. Interpretation: Although adherence was high among individuals in stable relationships taking ART for prevention, mental health and adherence covaried. Assessing and intervening on mental health in the context of promoting adherence to ART as prevention should be explored. Adherence and couples' counseling, feedback about viral suppression, and/or altruism may also help explain the magnitude of adherence observed. Abstract : Supplemental Digital Content is Available in the Text.